Strategizing: The challenges of a practice perspective - Jarzabkowski, Paula; Balogun, Julia; Seidl, David (Human relations (New York), 2007)
While the strategy-as-practice research agenda has gained considerable momentum over the past five years, many challenges still remain in developing it into a robust field of research. In this editorial, we define the study of strategy from a practice perspective and propose five main questions that the strategy-as-practice agenda seeks to address. We argue that a coherent approach to answering these questions may be facilitated using an overarching conceptual framework of praxis, practices and practitioners. This framework is used to explain the key challenges underlying the strategy-as-practice agenda and how they may be examined empirically. In discussing these challenges, we refer to the contributions made by existing empirical research and highlight under-explored areas that will provide fruitful avenues for future research. The editorial concludes by introducing the articles in the special issue.